A core-level spectroscopic investigation of the preparation and electrochemical cycling of nitrogen-modified carbon as a model catalyst support. Issue 2 (8th December 2015) - Christensen, Steven T.; Nordlund, Dennis; Olson, Timothy; Hurst, Katherine E.; Dameron, Arrelaine A.; O'Neill, Kevin J.; Bult, Justin B.; Dinh, Huyen N.; Gennett, Thomas
Abstract : X-ray absorption spectroscopy shows the dramatic changes a nitrogen modified carbon support can undergo due to electrochemical processes. Abstract : The synthesis and electrochemical cycling of platinum–ruthenium nanoparticles sputtered onto nitrogen-implanted highly-oriented-pyrolytic-graphite (HOPG) was studied with soft X-ray spectroscopy. The near edge X-ray absorption fine structure (NEXAFS) of the carbon 1s, nitrogen 1s, and oxygen 1s transitions were measured as a function of sample preparation and electrochemical cycling. The NEXAFS of the C 1s edge indicate defect formation in the graphitic (sp 2 ) network of the carbon support due to implantation. The primary nitrogen species include pyridinic, nitrilic, and graphitic with no evidence of pyrrolic nitrogen. Upon exposure to ambient conditions, the carbon defects react and produce both –CO and –C–OH species. Sputtering Pt : Ru and subsequent air exposure introduces more defects that react with ambient oxygen to increase the number of –CO species. The samples also show signs of oxidization after implantation. Electrochemical cycling of the samples restores the C 1s fine structure associated with graphitic (sp 2 ) carbon and alters the concentration of nitrogen species associated with the nitrile functional groups. The cycling also induces platinum oxidation and ruthenium loss, determined from X-ray photoelectron spectroscopy (XPS) of the Pt 4f, Ru 3d and Ru 3p. The results provide useful evidence of the types of nitrogen species that are present after electrochemical processes which can be used in the rational design of future electrocatalyst systems.